Is the impact of environmental regulation on enterprise green technology innovation incentives or inhibitions? A re-examination based on the China meta-analysis - Ren, Gaofei; Chen, Yaoyao (Frontiers in Environmental Science, 2023)
Environmental regulation and green technology innovation are the important driving forces to realize the peak of carbon and carbon neutralization strategy. However, whether environmental regulation can promote or inhibit green technology innovation, the existing literature research has not yet formed a consistent conclusion, and there is no literature to conduct a unified analysis of the relationship between the two. Based on 39 independent research papers published from 2006 to 2020, this paper integrates and analyzes the relationship between environmental regulation and enterprise green technology innovation and its corresponding dimensions in the context of China. The results show that there is a significant positive correlation between environmental regulation and enterprise green technology innovation overall. There is a significant positive correlation between command-control environmental regulation, tax-based environmental regulation, enterprise green product innovation, green process innovation, and green R&D investment, but there are differences in intensity. At the same time, this study also found that the types of environmental regulation, industry characteristics, and economic regions moderate the relationship between environmental regulation and enterprise green technology innovation. These findings further clarify the differences of understanding on the relationship between environmental regulation and green innovation of enterprises, provide a new perspective for the inconsistency of existing relevant research conclusions, and provide new supporting evidence for the Porter hypothesis, which has important implications for the government to optimize environmental regulation policies to promote the development of green economy.